Hepatitis C Diagnosis and Treatment Among Indigenous People in a Canadian Context: Challenges and Community-Led Solutions - Kate P. R. Dunn; Mia J. Biondi; Samuel S. Lee (Microorganisms)
The historical and ongoing impacts of the influence of colonization are experienced by Indigenous people in systemic racism, inequity in healthcare access, and intergenerational trauma; originating in the disruption of a way of life and seen in a grief response, with links to disparate hepatitis C virus (HCV) prevalence. Despite this, the focus often remains on the increased incidence without a strengths-based lens. Although HCV is a global concern that can result in cirrhosis, liver failure, or cancer, diagnosing and linking people to care and treatment early can prevent advanced liver disease. Efforts to engage certain priority populations are occurring; however, historical context and current practices are often forgotten or overlooked. This is especially true with respect to Indigenous people in Canada. This review considers the published literature to elucidate the context of historical and ongoing colonizing impacts seen in the current HCV treatment gaps experienced by Indigenous people in Canada. In addition, we highlight strengths-based and Indigenous-led initiatives and programming that inspire hopefulness and steps toward community-engaged solutions to meet the World Health Organization Goals of eliminating HCV as a public health threat.